PENGARUH LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP PROFIT UMKM DAN KEBERLANGSUNGAN UMKM DI KABUPATEN SERANG - Yulaikah, Yulaikah; Nurliana, Lia; Kurnianingsih, Asih (Universitas La Tansa Mashiro, 2023)
MSMEs face capital constraints and business continuity due to restrictions on community activities, which have an impact on declining income levels. The purpose of this study is to find out how financial inclusion financial literacy impacts the survival of MSMEs in Kab. Attack and their productivity and income. As part of a quantitative research strategy, respondents are given a questionnaire. Purposive Sampling was used to collect samples from 79 MSMEs in Serang Regency that met the requirements of being actively managed and had been operating for more than one year. smallest square footage. To carry out data analysis procedures, Partial Least Square 3.0 (PLS) was used. According to the test results, financial inclusion has an impact on the performance/profits of MSMEs, business continuity, and financial literacy has an impact on the financial performance of MSMEs in Kab. Attack. The financial literacy factor has no effect on the continuity of MSME businesses.